2006
DOI: 10.1103/physrevb.73.094426
|View full text |Cite
|
Sign up to set email alerts
|

X-ray absorption near-edge spectroscopy study of Mn and Co valence states inLaMn1xCoxO3(x=0

Abstract: A systematic study of the valence states of Mn and Co in the perovskite series LaMn 1−x Co x O 3 ͑x = 0 to 1͒ by means of x-ray absorption near edge spectroscopy ͑XANES͒ at the K-edges is presented. The chemical shift and the evolution of the pre-edge features reveal a gradual increase of the average oxidation level of both, Mn and Co ions, with Co doping, which suggests that mixed valence states of Co 2+ /Co 3+ and Mn 3+ /Mn 4+ exist in the whole solid solution range. The relation of the results to the magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
46
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 23 publications
13
46
0
Order By: Relevance
“…In La 1−x Ca x MnO 3 manganites, systematic shifts in the absorption edge position of the Mn K-edge with a changing of composition have been reported [6,7]. In our case the position of the absorption edge is approximately constant throughout the series (Fig.…”
Section: Xanessupporting
confidence: 50%
See 1 more Smart Citation
“…In La 1−x Ca x MnO 3 manganites, systematic shifts in the absorption edge position of the Mn K-edge with a changing of composition have been reported [6,7]. In our case the position of the absorption edge is approximately constant throughout the series (Fig.…”
Section: Xanessupporting
confidence: 50%
“…The highest value of T c = 270 K has been obtained for La 2/3 Ca 1/3 MnO 3 [3]. X-ray absorption fine structure (XAFS) studies of the manganites La 1−x Ca x MnO 3 have been reported in a number of papers [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…This method consists in integrating the absolute value of the difference between sample spectrum and a reference spectrum. [27,34] whereas no spin transition is found on TbCoO 3 compound. In the latter, Co 3+ remains in LS state both at 300 K and 30 K, as observed in related compounds with heavier rare-earths on the A cation site.…”
Section: Methodsmentioning
confidence: 88%
“…[42][43][44][45][46][47] Principal component analysis and linear combination ͑LC͒ of XANES reference spectra to fit the experimental spectrum [45][46][47] were selected here as these approaches have proven to be reliable and sensitive tools for the determination of the type and relative amount of each component that contributes to the absorption spectrum of multicomponent systems, when the absorbance spectrum of each individual component significantly differs, and when proper reference compounds with similar structures, compositions, types of neighbors, and local symmetries as in the examined material can be used. A mean value of the oxidation state of each element in the Q800CAir samples was estimated by LC fitting of the L3 absorption edge and its derivative, using the spectra of the Reduced and Oxidized samples as references.…”
Section: Resultsmentioning
confidence: 99%